T-way testing : a test case generator based on melody search algorithm - Toh, Shu Yuen (2015)
Nowadays, the era of advanced technology has brought modern software systems into our daily life to satisfy the various needs of users. To ensure a well function of software systems without defects, software testing plays a dominant role on it. However, exhaustive testing is impossible that is required a huge amount of cost and time. This thesis is research on developing a T-Way Testing : A Test Case Generator Based On Melody Search Algorithm (TTT-MS) to generate optimum final test list. First, Inputs will be written into a text file and TTT-MS will read the inputs which are the number of Parameters, number of values for each Parameter, Parameter Names, Parameter Values Name and the Interaction Strength (t) up to t=4. Next, TTT-MS will be executed through main algorithms to generate Parameters Interaction List, Parameter Values Interaction List, and finally generate final Test Cases based on Melody Search Algorithm. Basically, TTT-MS consists of four main procedures which are User Interface, Interaction List Generation, Test Case Generation and Mapping of Parameter Values in Symbolic Value to Actual Name. After the generation of Final test List through the execution of TTT-MS, the results are being evaluated and compared with other existing t-way strategies. Results shows that sometimes TTT-MS performed better than other existing strategies in certain data specification due to the behavior of optimization algorithms.